(untitled) (Bangladesh Journal of Botany, 2021)
Antifungal properties of Cucumis sativus, Portulaca oleracea, Malus baccata, Saxifraga flagillaris, Geranium wallichianum. and Monotheca buxifolia were evaluated against Alternaria, Acremonium, Verticillium, Pythium, and Trichoderma, using agar well-diffusion method. The crude ethanolic extract of G. wallichianum showed the highest antifungal activity followed by P. oleracae and S. flagillaris. The dichloromethane fraction of G. wallichianum showed the highest antifungal activity against Acremonium (28 mm), Alternaria (20.50 mm) and Trichoderma (20 mm). The n-hexane fraction of C. sativus showed the maximum antifungal activity (20 mm) against Pythium. The present findings demonstrated that six selected plants contain precious natural products for treating infectious diseases and can be used to isolate chemical compounds for future drug sources. Bangladesh J. Bot. 50(2): 441-443, 2021 (June)